Development of the digital communication culture of prospective teachers based on digital etiquette training in the context of Kazakhstan - Аbdigapbarova Ulzharkyn; Syzdykbayeva, Aigul; Aitenova, Elmira; Nishanbayeva, Sabira; Nurgaliyeva, Saniya (Journal of Education and e-Learning Research, 2025)
This study examines the impact of digital etiquette training on the development of a digital communication culture among future teachers by providing new perspectives and access to scientific knowledge in the field of digital etiquette. A mixed-methods approach was used both before and after the test. The study included 115 respondents. The preliminary testing between the groups showed that both groups were at the same level in terms of communicative culture indicators. Additionally, participants had no prior knowledge of digital etiquette. An authors’ programme was created specifically for the course and implemented to help students become more skilled with technology. A set of measures was carried out to develop a digital communicative culture through the means of netiquette and the introduction of technology for individualization and personalization of learning. This study found the impact of digital etiquette on the development of a digital communication culture in future teachers by providing new perspectives and access to scientific knowledge in the field of digital etiquette as well as the practical application of this knowledge to support cultural digital interaction.